SELFCARE DAN KEKAMBUHAN HIPERTENSI PADA LANSIA - Erpandi; Haryanto; Lukita, Yenni (Jurnal Riset Keperawatan dan Kesehatan, 2024)
Background: Hypertension is one of the most common chronic diseases among the elderly and remains a leading cause of death in Southeast Asia. The increasing number of elderly hypertensive patients in Indonesia, including in Kayong Utara Regency, highlights the importance of self-care behavior to prevent recurrence. Objective: To describe the self-care behavior of elderly patients in preventing hypertension recurrence at the Outpatient Clinic of Sultan Muhammad Jamaludin I Regional Hospital, Sukadana. Methods: This study employed a descriptive quantitative design with a cross-sectional approach. A total of 92 elderly patients with hypertension were selected using a purposive sampling technique. Data were collected using a questionnaire covering five aspects of self-care: medication adherence, diet management, stress control, physical activity, and spirituality/worship. Results: Most respondents were aged 45–59 years (52.2%) and female (58.7%). A total of 91.3% of respondents were non-adherent to antihypertensive medication, while other self-care behaviors were categorized as good: emotional control (63%), physical activity (68.5%), dietary management (69.6%), and spirituality/worship (67.4%). Conclusion: The overall self-care behavior of elderly patients in preventing hypertension recurrence was generally good, except for medication adherence, which remained low. Continuous education and family support are needed to improve treatment adherence and prevent recurrence.